Perceived Importance of Professional Competencies for Admission to the College of Kinesiologists of Ontario. - Prevost, Julien R. C.; Kpazaï, Georges; ATTIKLEME, KOSSIVI; ., . (My University, 2015)
Background: For more than a decade, the development of professional competencies has been at the heart of curriculum reforms in Education and Health care training worldwide. Reference documents of competencies have been developed in Australia (Brownie, Thomas, McAllister, & Groves, 2014), Canada (Boucher & Ste-Marie, 2013; Royal College of Physicians and Surgeons of Canada, 2005), United-States (Hurd & Buschbom, 2010), and in Europe (Battel-Kirk, Van der Zanden & al., 2012). In most of these reference documents, the number of professional competencies that a professional must acquire does not exceed twenty. However, in the field of kinesiology, the College of Kinesiologists of Ontario (CKO) (2013) has defined 54 professional competencies required for admittance to the College. Objective: The purpose of this research project aims to identify, from the standpoint of university instructors who teach in a kinesiology program, the professional competencies that are considered the 17 most relevant from those suggested by CKO. Methodology: Participants (N=23) were required to complete an online survey on the domain www.SurveyMonkey.com in order to determine the competencies deemed most important by them. Results: The quantitative data obtained through the use of the surveys allowed for a list of 17 competencies to be retained at the end of the study. The qualitative data provided by the participants supported and complemented the quantitative data. Conclusion: The competencies retained in this study undoubtedly represented the views of all the participants in regards to the essential competencies that a kinesiologist should be able to demonstrate upon admission to the College of Kinesiologists of Ontario.
Keywords: Professional competencies; Curriculum; Kinesiology